Elucidation of Structure–Activity Relations in Proton Electroreduction at Pd Surfaces: Theoretical and Experimental Study. Issue 30 (20th June 2022) - Schmidt, Thorsten O.; Ngoipala, Apinya; Arevalo, Ryan L.; Watzele, Sebastian A.; Lipin, Raju; Kluge, Regina M.; Hou, Shujin; Haid, Richard W.; Senyshyn, Anatoliy; Gubanova, Elena L.; Bandarenka, Aliaksandr S.; Vandichel, Matthias
Abstract: The structure–activity relationship is a cornerstone topic in catalysis, which lays the foundation for the design and functionalization of catalytic materials. Of particular interest is the catalysis of the hydrogen evolution reaction (HER) by palladium (Pd), which is envisioned to play a major role in realizing a hydrogen‐based economy. Interestingly, experimentalists observed excess heat generation in such systems, which became known as the debated "cold fusion" phenomenon. Despite the considerable attention on this report, more fundamental knowledge, such as the impact of the formation of bulk Pd hydrides on the nature of active sites and the HER activity, remains largely unexplored. In this work, classical electrochemical experiments performed on model Pd(hkl) surfaces, "noise" electrochemical scanning tunneling microscopy (n‐EC‐STM), and density functional theory are combined to elucidate the nature of active sites for the HER. Results reveal an activity trend following Pd(111) > Pd(110) > Pd(100) and that the formation of subsurface hydride layers causes morphological changes and strain, which affect the HER activity and the nature of active sites. These findings provide significant insights into the role of subsurface hydride formation on the structure–activity relations toward the design of efficient Pd‐based nanocatalysts for the HER. Abstract : Using a combination of experimental and theoretical approaches, the structure–activity relations that govern the complex electrochemical processes for the hydrogen evolution reaction (HER) on Pd electrodes is reported. The formation of subsurface hydride results in morphological changes, inducing a strain, which affects the activity toward the HER.